Visitor satisfaction and development effectiveness in red tourism: evidence from Guangzhou - Li, Kun; Mei, Wen-Bing; Huang, Yi-Zhe (Frontiers in Psychology, 2025)
Promoting red historical culture, fostering patriotic sentiment, and strengthening cultural confidence are central tasks in China’s cultural development in the new era. As both a cradle and a vanguard of China’s modern democratic revolution, Guangzhou is endowed with abundant red historical and cultural resources. Assessing the effectiveness of red tourism site development in Guangzhou thus carries significant practical implications. Drawing on expert interviews, questionnaire surveys, and big-data statistical analysis, and using the importance–performance analysis (IPA) quadrant method, this study reaches the following conclusions: (1) The development effectiveness of Guangzhou’s red tourism sites constitutes a multidimensional composite structure, comprising three critical dimensions—red cultural connotations, management behavioral norms, and landscape and facilities—encompassing 27 specific indicators; (2) the three dimensions exert differential effects on visitor satisfaction, with red cultural connotations (β = 0.455) emerging as the most influential, followed by management behavioral norms (0.209) and landscape and facilities (0.114); (3) while visitors generally hold high expectations regarding the development of Guangzhou’s red tourism sites, their actual perceptions fall short, revealing a significant negative “expectation–perception” gap. Based on these findings, we propose targeted strategies to enhance site development effectiveness and visitor satisfaction, offering practical and theoretical insights for improving red tourism site development.